Controlled Release of Gentamicin from Electrospun Poly(Vinyl Alcohol)/Gelatin Nanofibers: The Effect of Crosslinking Time Using Glutaraldehyde Vapor. Issue 5 (2nd February 2023) - Baykara, Dilruba; Pilavci, Esra; Cesur, Sumeyye; Ilhan, Elif; Ulag, Songul; Sengor, Mustafa; Kijeńska‐Gawrońska, Ewa; Gunduz, Oguzhan
Abstract: In this study, polyvinyl alcohol (PVA), gelatin (GEL) and gentamicin (GEN) were used and 13PVA/0.5GEL/GEN nanofibers were fabricated with the electrospinning method. These nanofibers were crosslinked chemically with glutaraldehyde (GA) at different time intervals (2, 3, 4, 5, 5.5 and 6 h) to observe the crosslinking effect on the properties of the nanofibers. Morphological analysis reported that as the crosslinking time increased, the nanofiber diameters also increased from 369.26 nm (non‐crosslinked) to 447.72 nm (6 h/crosslinking), respectively. The thermal characterization results demonstrated that crosslinking with different times noticeably shifted the thermal points.The tensile testing results proved that application of crosslinking enhanced the mechanical strength of the nanofibers from 3.31 MPa (non‐crosslinked) to 5.8 MPa (5.5 h/crosslinking), respectively. The GEN release profiles from the nanofibers showed similar behaviors under crosslinking and indicated that the crosslinking time did not have a significant effect on the amount of the GEN released. Abstract : In this study, polyvinyl alcohol (PVA), gelatin (GEL) and gentamicin (GEN) were used and 13PVA/0.5GEL/GEN nanofibers were fabricated with the electrospinning method. These nanofibers were crosslinked chemically with glutaraldehyde (GA) at different time intervals (2, 3, 4, 5, 5.5 and 6 h) to observe the crosslinking effect on the properties of the nanofibers.